Hepatoprotective Effect Of Cassia Sophera Leaves Extract Against Paracetamol Induce Hepatic Injury In Rats. - WANKHADE P.W; NAGORE D. H; KOTAGALE N. R; TURASKAR A. O; MORE S. M (International Journal of Pharma and Bio Sciences, 2011)
Ethanol extract of Cassia sophera (Caesalpiniaceae) was evaluated for hepatoprotective activity in rats. The plant extract (500 mg/kg, p.o.) showed a remarkable hepatoprotective activity against paracetamol induced hepatotoxicity as judged from the serum markers for liver damage. Paracetamol induced a significant rise in aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP), total bilirubin and decrease in total protein. Treatment of rats with ethanol extract (500 mg/kg) significantly altered serum marker enzymes levels to near normal against paracetamol treated rats. The activity of the extract was comparable to the standard drug Liv-52 (5 ml/kg, p.o.) Histopathological changes of liver sample were compared with respective control. Results indicate that Cassia sophera possesses hepatoprotective effect on paracetamol induced hepatotoxicity in rats.